Labour Market Processes, Competences and Their Changes During the Pandemic - Varga, Erika; Szira, Zoltán (Acta Carolus Robertus, 2022)
It may sound commonplace, but it is still general truth when we say that the driving force of any economy is labour, which is primarily determined by the quantity and quality of human resources.  Balancing supply and demand on the labour market is one of the most important and fundamental tasks of human resource management, which is not easy even under 'normal' circumstances - not to mention the pandemic of recent years. Beyond its health dimension, the Covid-19 pandemic has unfortunately left behind serious political, social, demographic and economic problems that are not easy to eradicate or resolve.Our objective is to examine one of the above-mentioned areas of HR, namely, recruitment and selection, and to follow the changes in this pandemic, during which HR professionals have faced and continue to face new and perhaps unprecedented challenges. In short, we are going to point out the new skills and competences that have come to the foreground as a result of the pandemic, while others were pushed into the background.In this article we seek to answer the following questions:What are these challenges for employers and employees? Can such an epidemic cause a complete structural change in recruitment and selection processes? How does the epidemic hinder jobseekers in their job search in a different way than before? Will jobseekers who become unemployed during the epidemic find work sooner or later? In which areas has there been a surge in job demand and where is there a significant decrease in job demand compared to 2019?
Keywords: labour market; recruitment; selection, competence; COVID-19; job search; jobseekers